2021
DOI: 10.3389/fvets.2020.599418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensive Fattening With Total Mixed Rations on Carcass Characteristics, Meat Quality, and Meat Chemical Composition of Yak and Mechanism Based on Serum and Transcriptomic Profiles

Abstract: The objective of this study was to investigate the effects of intensive fattening with total mixed rations (TMR) on carcass characteristics, meat quality, and chemical composition of the yak meat. Theoretical data has been provided for evaluating the quality of yak meat during natural grazing and short-term fattening. Based on the analysis, we found that in fattening yak, the carcass weight (CWT) was increased by 106.43%, whereas the cooking loss, tenderness, and drop loss were significantly improved due to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…The proximate chemical composition of the muscle tissue was determined according to the procedure described by Liu et al [ 15 ], and the samples to be tested were thawed at 4 °C for 24 h before testing and were analyzed in the same laboratory. Moisture was measured using the direct drying method (at 105 °C), protein was tested using the Kjeldahl method, fat was determined using the Soxhlet extraction method, and the ash content was determined via ashing samples in a muffle furnace at 500 °C for 24 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proximate chemical composition of the muscle tissue was determined according to the procedure described by Liu et al [ 15 ], and the samples to be tested were thawed at 4 °C for 24 h before testing and were analyzed in the same laboratory. Moisture was measured using the direct drying method (at 105 °C), protein was tested using the Kjeldahl method, fat was determined using the Soxhlet extraction method, and the ash content was determined via ashing samples in a muffle furnace at 500 °C for 24 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Amino acids were quantified based on the Chinese recommended standards (GB 5009 124-2016) described by Liu et al and Dai et al [ 15 , 17 ], with some modifications. The protein was broken up into free amino acids by acid hydrolysis at 105 °C for 22 h and then separated using an AJS-01 amino acid special analytical column (C18, 3 μm, 4.6 × 150 mm; Welch Technology Co., Ltd., Shanghai, China) and derivatized using a ninhydrin solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of supplementary feeding could be an effective way to reduce the gap between the production of high-quality yak meat and increased market demand ( 4 ). Liu et al ( 5 ) reported that fattening yaks with a total mixed diet in the cold season can improve the yield and quality of the yak meat. Zhang et al ( 4 ) reported that supplementing a diet with high-protein in early-weaned yaks could increase intramuscular fat accumulation.…”
Section: Introductionmentioning
confidence: 99%